USAHA PEMBERDAYAAN LANSIA SECARA FISIK MELALUI PROGRAM PELATIHAN SENAM LANSIA BUGAR (SLB) - Listyarini, A. Erlina (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Pengabdian  pada  Masyarakat (PPM)  in the purpose to  creating  pre intruktur senam Lansia Bugar (SLB) in sub district in the Gantiwarno of district and Klaten of regency. PPM has been did on July,16-17, 2010 in the sport building of Jabung sub district, Gantiwarno of district and Klaten of regency. PPM  in  using  of  speaking,  demonstrate,  command  and  reciprocal methods. The practice has been did in 16 hour. Practicing such as physical fitness of theory, gym of training principle, prevent of injury principle, and practical such as SLB. The instrument such as of reactive, participation, absent and eager to a move and the technical truly of SLB. From the result of practice has been fended 5 people (12%) in excellent categories, 36 people (88%) in good categories. From in this practice, have been did competition with our sub district and the instantion to celebrating independence day of Klaten regency and also in celebrate independence day of RI as result : 1st winner is  Unit Pendidikan Tingkat Daerah (UPTD), 2nd winner is Towangsan sub district, an 3rd winner is jabung sub district